Rice extract: Antioxidant activities and formulations - Naphatson Chanthathamrongsiri, Chadaporn Prompanya, Nattawut Leelakanok, Nadechanok Jiangseubchatveera, Tistaya Semangoen, Parinyaporn Nuurai, Witoon Khawsuk, Arpa Petchsomrit (Journal of Applied Pharmaceutical Science, 2022)
The objective of this study was to evaluate the potential use of the Thai black glutinous rice grain (RG) and black glutinous rice bran (RB) extract in cosmeceutical products. The ethanolic extracts were prepared. Anthocyanin, phenolic, and flavonoid contents in the extracts were determined, and antioxidant activities were evaluated using 2,2-Di(4-tert-octylphenyl)-1-picrylhydrazyl, 2,2?-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid), and ferric reducing antioxidant power assays. The RB extract exhibited higher total phenolic (129.03 ± 2.44 μg of gallic acid equivalent/mg extract) and flavonoid (7.56 ± 0.40 μg of quercetin equivalent/mg extract) contents than the RG extract. In addition, the antioxidant activities of the RB extract were superior to the activities of the RG extract. Therefore, the RB extract was selected for loading into the water- and oil-based formulations. The stability testing consisted of centrifugation and six heating-cooling cycles. All formulations were stable without noticeable phase separation or aggregation after the stability testing. In addition, the pH values ranged between 5 and 5.5, which was proper for skin application. Our findings indicate that the RB extract is a source of phenolic compounds with antioxidants and suggest that this extract might be a promising active component in skincare products.
Keywords: Black glutinous rice bran, phenolic contents, flavonoid contents, antioxidant, formulation